The investigation of the wear of composite coatings of Zn-15Cu-20Al-5O-5C and Zn-30Cu-20Al-5O-10C on the surface of a crankshaft bearing - Hazar, H.; Cihan, O. (Natl Inst Optoelectronics, 2014)
In this study, 6LD400 Lombardini crankshaft bearing internal surface was coated with two different zinc based alloys by atmospheric plasma spraying method. Coatings and matrix microstructure were analyzed with the Scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS). When the images of SEM samples are examined, a pore structure with wear tracks is seen. In wear test, in the loads applied, the least weight loss was found in the bearing coated with Zn-15Cu-20Al-5O-5C alloy. Average hardness value is found to be 52,5 HV which is accepted as the ideal bearing surface structure in bearing coated with Zn-30Cu-20Al-5O-10C alloy.
Keywords: Zinc; Copper; Aluminum; Crankshaft bearing; Atmospheric plasma spray